2013
DOI: 10.1016/j.jpha.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography tandem mass spectrometry method for the estimation of lamotrigine in human plasma: Application to a pharmacokinetic study

Abstract: A reliable, selective and sensitive liquid chromatography tandem mass spectrometry method was developed and validated for the quantification of lamotrigine in human plasma using lamotrigine-13C3, d3 as an internal standard. Analyte and internal standard were extracted from human plasma by solid-phase extraction and detected in positive ion mode by tandem mass spectrometry with electrospray ionization (ESI) interface. Chromatographic separation was performed on a Chromolith® SpeedROD; RP-18e column (50−4.6 mm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The calibration curve obtained was linear and meets the requirements of the correlation coefficient (r) value greater than 0.98. 15 The results of the calibration curve experiment showed that the %diff obtained fulfilled the requirements. Data of O 6 -methylguanine inter-day calibration curves are shown in Table 4 .…”
Section: Resultsmentioning
confidence: 65%
“…The calibration curve obtained was linear and meets the requirements of the correlation coefficient (r) value greater than 0.98. 15 The results of the calibration curve experiment showed that the %diff obtained fulfilled the requirements. Data of O 6 -methylguanine inter-day calibration curves are shown in Table 4 .…”
Section: Resultsmentioning
confidence: 65%
“…Calibration standards were prepared and analyzed by plotting the peak area ratios of the analyte to the internal standard versus the nominal concentration in triplicate. Calibration curves were considered acceptable when the correlation coefficient ( r ) was greater than 0.98 for biological matrix,[ 14 ] and the bias of the calculated concentrations was within ±15% of the nominal concentrations, except the LLOQ with an allowed deviation of ±20%.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…Calibration curve was calculated with weighted linear curve fit equation, 1/ x . [9] Calibration curves were considered acceptable when the correlation coefficient ( r ) was greater than 0.98 for biological matrix[10] and the bias of the calculated concentrations was within ±15% of the nominal concentrations, except the LLOQ with an allowed deviation of ±20%. [8]…”
Section: Methodsmentioning
confidence: 99%